Strategies For Using Learning Media To Increase Stimulus For Reading Comprehension And Recognizing Surrounding Objects Among Children - Hanayanti, Citra Siwi; Subroto, Desty Endrawati; Fujiono, Fujiono; Roda'i, Muhammad; Rizqi, Vini (Jurnal Scientia, 2024)
The importance of exploring strategies for using learning media in enhancing the stimulus of reading comprehension and recognition of objects around children. The method used is literature review, which involves analyzing various studies and scientific sources related to this topic. The results showed that interactive learning media such as educational apps, picture books, and augmented reality (AR) can significantly improve children's reading comprehension and object recognition. However, challenges such as lack of access to quality media and teachers' ability to use them need to be addressed. Recommendations include improving access to quality media, teacher training and parental involvement in the learning process.